The SMEs Performance: Mediation of Ambitious Entreprenuer - Novari, Eri (International Journal of Psychosocial Rehabilitation, 2020)
Research study focuses on examining Human Resources behavior with market orientation, ambitious entrepreneur, and SMEs performance. In which the final objective is evaluating SME's performance through an entrepreneur in Indonesia. Research conducted in Indonesia with the sample used is 133, namely the entrepreneur of SMEs. Data from an entrepreneur obtained through a questionnaire, and it processed by using SmartPLS with a path analysis technique. The research result emphasized through a model test of the research hypothesis. Research results known that market orientation has a positive impact on an ambitious entrepreneur. Besides that, an ambitious entrepreneur can influence the improvement of SME's performance. However, market orientation cannot truly directly good impact on the improvement of SME's performance. In evaluating SMEs performance is needed ambitious entrepreneur that is supported by the soul of market orientation. And it is not in examining the improvement of SME's performance, which does not focus on market orientation directly. Information is related to Human Resources behavior, which is market orientation and ambitious entrepreneur can be a suggestion for SMEs in determining policy on a business strategy, which involves human resources. From the government side, taking a policy for SMEs can learn an entrepreneur’s behavior, and it makes that policy can improve SMEs in Indonesia. It found the mediation model of an ambitious entrepreneur in improving the relationship of market orientation to SME's performance.